Women's Perception of Air Pollution and Associated Health Hazard Aspects - A Study in Low-Income Urban Space in Bangladesh (Global Journal of Human-Social Science, 2022)
This paper explores women's perception of air pollution and associated health hazards they experience in the low-income urban community of Bangladesh. Following the qualitative methodology, the research employs primary and secondary data to scrutinize the linkage betweenair pollution and women's health. Data analysis in both percentages and an interpretive thematic approach was supported by two focus group discussions and 15 in-depth interviews conducted in the Mridhabari area in Matuail -one of the environmentally vulnerable areas in urban Bangladesh.The findings show that poor women's comprehension of emissions of greenhouse gases and air pollutants is unsound and erroneous. Though women suffer from multiple physical, psychological, and reproductive health sicknesses due to their stay in a place with poor air quality, their apathetic outlook on health, reinforced by socially accepted gender norms, ignorance, misconception, and blind faith, contributes to avoiding seeking any medical treatment while getting sick.
Keywords: air pollution; health hazards; low-income urban community; poor women; Bangladesh